Pelatihan Manajemen Usaha Bagi Kelompok Usaha Bersama (KUBE) Jupiter Jaya Di Dusun Mavilla Rengganis Kabupaten Lombok Barat - Baiq Herdina Septika; Tama Krisnahadi; Menik Aryani; Yayang Erry Wulandari; Ira Dianti (Jurnal Pengabdian UNDIKMA, 2021)
The purpose of this service activity is to increase the motivation of Community Business Groups and the competitiveness of products by providing business management training for Jupiter Jaya Joint Business Group (KUBE) in Mavilla Rengganis Village, West Lombok Regency. The methods of implementing this activity wereby lectures, discussions and mentoring. The lectures were consisted of delivering material on business management, namely packaging management, labeling management and business financial management. The participants in this activity were 10 members of Jupiter Jaya KUBE. For financial management, partners were given training in simple financial bookkeeping and given assistance in making business bookkeeping.The result of this service activityis that most of the participants can comprehend business financial management. It can be seen that more than 90% of participants are able to make financial bookkeeping. In addition, the partners also agreed to use pouch stand for fish crisp packaging. This is because the stand pouch is more practical in packaging, strong in design, very flexible in shape, economical in price, and more modern and attractive in appearance. For product brands, the partners also agreed to name the fish crisp brand as dua sekawan.